2021
DOI: 10.21037/tlcr-20-781
|View full text |Cite
|
Sign up to set email alerts
|

Integrating endobronchial ultrasound bronchoscopy with molecular testing of immunotherapy biomarkers in non-small cell lung cancer

Abstract: Immunotherapy has transformed treatment of advanced non-small-cell lung cancer (NSCLC) patients leading to remarkable long-term survival benefit. However, only about 20% of advanced NSCLC patients typically respond to immune checkpoint inhibitors (ICIs) that target the PD-1/PD-L1 pathway.The only validated biomarker for ICI therapy is the PD-L1 immunohistochemistry (IHC) test, which is considered an imperfect assay due to several variables including availability and integrity of tumour tissue, variability in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Radial probe EBUS is used to sample pulmonary parenchymal lesions, a unique technique that incorporates both cytologic and histologic sampling. Additionally, EBUS-TBNA sampling has been used to characterise the immunophenotypic properties of tumourdraining lymph nodes in not-small cell lung cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…Radial probe EBUS is used to sample pulmonary parenchymal lesions, a unique technique that incorporates both cytologic and histologic sampling. Additionally, EBUS-TBNA sampling has been used to characterise the immunophenotypic properties of tumourdraining lymph nodes in not-small cell lung cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…This method enables amplification of the signal for the detection of the target protein with light microscopy ( 28 ). Additionally, IHC can be performed effectively on small tissue samples such as those obtained via EBUS ( 29 ).…”
Section: Immunohistochemistry-based Methodsmentioning
confidence: 99%
“…In the case of metastatic tumors with greater than 50% PD-L1 expression, pembrolizumab can be used as the first-line treatment, while nivolumab is the drug of choice for secondline treatment, regardless of PD-L1 expression [59] . It is noteworthy that higher PD-L1 expression is generally linked to better results of ICI therapy [60] , yet burdens always lie ahead. Low RR and survival of patients going through ICI therapy, specifically those with metastatic and advanced NSCLC, created new urges for medicine [61] .…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%
“…Combinational therapy is the next solution. Chemotherapy, the very basic and wellknown treatment strategy for cancer, has shown improved results in combination with pembrolizumab [60] . A study conducted recently reported meaningful improvement in objective RR and progression-free survival (PFS) after using tiragolumab in combination with atezolizumab compared to atezolizumab alone [64] .…”
Section: Non-small Cell Lung Cancermentioning
confidence: 99%